Organizational climate as a predictor to job satisfaction of new faculties in three public Universities of Malaysia. - Abdul Wahat, Nor Wahiza (2009)
Attached to three public which are also research universities of Malaysia, a total of 117 new faculties from various social and hard sciences disciplines have been investigated to draw upon important findings on their perceived organizational and job satisfaction levels, as well as the influence that their perceived organizational climate has on job satisfaction. A survey based on the conceptual framework which integrated the Theory of Work Adjustment (Dawis and Lofquist, 1984) and Person-Environment Perspective was conducted to meet the objectives of the study. Data were analyzed using descriptive, Pearson correlation and simple regression analyses. Results showed that most new faculties embraced high level of perceived organizational climate but moderate job satisfaction levels. There was a significant, positive relationship between perceived organizational climate and job satisfaction. Both the relationship climate and development climate dimensions correlated significantly with job satisfaction. Perceived organizational climate was further identified as predictor of job satisfaction for new faculties serving in the three public, research universities. Based on the findings, it is highly recommended for the universities to adopt non-formal mentoring system as an effective organizational mechanism to establish and sustain harmonious relationships between new faculties and their senior colleagues.